Regional Voices: Delving into the Ethnolinguistic Analysis of the Indigenous People’s Languages - Princess Sarah Camado; Airich Angel Mahinay; Meja Fernandez; Ana Mae Monteza (English Language and Literature in Education Journal, 2025)
This study investigates how Indigenous languages serve as vehicles for cultural preservation by examining the Blaan and Manobo languages through an ethnolinguistic lens, with particular attention to their syntactic and semantic structures. Employing a qualitative approach, the research conducted detailed textual analyses of traditional songs, proverbs, and oral narratives to uncover linguistic patterns that encode cultural values, social norms, and communal knowledge. Findings reveal that both languages predominantly exhibit a Subject-Verb-Object (SVO) word order, with songs employing simpler sentence structures to facilitate memorability and communal performance, while proverbs utilize more complex syntactic constructions to convey nuanced moral and ethical lessons. Analysis further highlights the central role of divine and communal forces in shaping cultural narratives, demonstrating that language functions as a medium for transmitting knowledge, regulating social behavior, and sustaining the interconnected relationship among society, nature, and spiritual beliefs. Beyond linguistic structure, the study underscores the broader significance of Indigenous language preservation for educational inclusion, empowerment of marginalized communities, and alignment with Sustainable Development Goals, particularly SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities). The research advocates for future investigations into community-led language revitalization initiatives and the strategic use of digital technologies to support the documentation, teaching, and continued vitality of Indigenous languages, reinforcing their role as critical instruments for identity, knowledge transmission, and social equity.